Repair of the degenerate retina by photoreceptor transplantation - Barber, Amanda C. (National Academy of Sciences, 2013)
Despite different aetiologies, age-related macular degeneration and most inherited retinal disorders culminate in the same final common pathway, the loss of photoreceptors. There are few treatments and none reverse the loss of vision. Photoreceptor replacement by transplantation is proposed as a broad treatment strategy applicable to all degenerations. Recently, we demonstrated restoration of vision following rod-photoreceptor transplantation into a mouse model of stationary night-blindness, raising the critical question of whether photoreceptor replacement is equally effective in different types and stages of degeneration. We present a comprehensive assessment of rod-photoreceptor transplantation across six murine models of inherited photoreceptor degeneration. Transplantation is feasible in all models examined but disease type has a major impact on outcome, as assessed both by the morphology and number of integrated rod-photoreceptors. Integration can increase (Prph2(+/Δ307)), decrease (Crb1(rd8/rd8), Gnat1(−/−), Rho(−/−)), or remain constant (PDE6β(rd1/rd1), Prph2(rd2/rd2)) with disease progression, depending upon the gene defect, with no correlation with severity. Robust integration is possible even in late-stage disease. Glial scarring and outer limiting membrane integrity, features that change with degeneration, significantly affect transplanted photoreceptor integration. Combined breakdown of these barriers markedly increases integration in a model with an intact outer limiting membrane, strong gliotic response, and otherwise poor transplantation outcome (Rho(−/−)), leading to an eightfold increase in integration and restoration of visual function. Thus, it is possible to achieve robust integration across a broad range of inherited retinopathies. Moreover, transplantation outcome can be improved by administering appropriate, tailored manipulations of the recipient environment.